Learning force patterns with a multimodal system using contextual cues. Issue 110 (February 2018) - Rodríguez, Jorge; Gutiérrez, Teresa; Portillo, Otniel; Sánchez, Emilio J.
Highlights: A new interaction technique based on contextual information using a multimodal system for force pattern learning is proposed. Using the contextual information approach, the trainees obtain information about the evolution of their performance along the time (helping to correct the errors). The findings suggest that the contextual information provides a better trainee's performance than the punctual information. One drawback of the training strategies based on punctual feedback is the difficulty that users have in interpreting the information. The contextual approach could be used to extend the capabilities of haptic training procedures based on haptic guidance to provide information about the level of force to be applied during the execution of a specific task. Abstract: Previous studies on learning force patterns (fine motor skills) have focused on providing "punctual information", which means users only receive information about their performance at the current time step. This work proposes a new approach based on "contextual information", in which users receive information not only about the current time step, but also about the past (how the target force has changed over time) and the future (how the target force will change). A test was run to compare the performance of the contextual approach in relation to the punctual information, in which each participant had to memorize and then reproduce a pattern of force after training with a multimodal system. The findings suggest that the contextual approach is a useful strategy for force pattern learning. The advantage of the contextual information approach over the punctual information approach is that users receive information about the evolution of their performance (helping to correct the errors), and they also receive information about the next forces to be exerted (providing them with a better understanding of the target force profile). Finally, the contextual approach could be implemented in medical training platforms or surgical robots to extend the capabilities of these systems.